Relieving Symptoms of Chronic Sinusitis in Children By Adenoidectomy - Hassan, Hussein M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: To determine the efficacy of adenoidectomy in relieving symptoms of chronic sinusitis in children. Patients and methods :A prospective study carried out on 35 patients who underwent adenoidectomy or Adeno-tonsillectomy between May 2004 and October 2005.The patient ages ranged from 3 to 12 years. Five patients were unavailable for follow-up and did not complete the study so they are excluded from. The pre-operative symptoms were Rhinorrohea, Nasal congestion, Headache, Postnasal drainage, Cough, Halitosis and Irritability. Also recorded was Mouth breathing, Fever and Frequent antibiotic use. Telephone interviews with the patient’s caregivers were conducted to collect information following the surgery regarding the presence of the same symptoms as well as an estimate of overall improvement. Follow-up ranged from 5 months to 1 year. Results :The most frequently reported symptoms before surgery were Rhinorrhoea, Nasal congestion, Mouth breathing, and Frequent antibiotic use. (26, 28, 24, 30 patients respectively). These numbers decreased following surgery to (11, 12, 6, 24 patients respectively) Complete or near complete symptom resolution was reported in 18 (60%) patients. Some improvement was reported in 6 (20%) patients. Minimal or no improvement was reported in another 6 (20%) patients. Conclusion In the majority of cases, symptoms of chronic sinusitis in children are relieved by adenoidectomy.